INNOVATION OF WATER HYACINTH-BASED HANDICRAFTS: A STRATEGY FOR COMMUNITY ECONOMIC ENHANCEMENT IN BANJARMASIN - Nor, Baseran; Kurniansyah, Kurniansyah; Abdillah, Muhammad; Nabila, Rizqah; Khadijah, Retno Salsabila (International Conference On Social Science Education, 2025)
Banjarmasin, frequently referred to as the "City of a Thousand Rivers," is endowed with substantial natural resources, among which is the prolific aquatic weed Eichhornia crassipes (water hyacinth). Although conventionally regarded as an environmental pest, this Research examines its viability as a sustainable raw material for local handicraft manufacturing, to stimulate economic advancement within the community. Using a qualitative methodology, data were collected through in-depth interviews and participant observation with the "Ilung Benawa" weaving collective. The study seeks to: (1) assess the economic implications of water hyacinth handicraft production; (2) pinpoint principal challenges in its development; and (3) advance strategic recommendations for sectoral growth. The findings reveal that water hyacinth is successfully converted into marketable goods—such as bags, hampers, and home décor—that provide supplementary income to local artisans, most of whom are women. Notwithstanding these benefits, persistent constraints include reliance on favourable weather for drying raw materials, limited product and colour diversification, and challenges in scaling production to meet broader market demand. Recommendations underscore the need for targeted governmental and non-governmental support through capital investment, technical training in dyeing and preservation, and the establishment of cooperative frameworks to bolster productive capacity and market penetration. In conclusion, this study affirms that valorising water hyacinth through handicraft production is a feasible dual-purpose strategy that advances both environmental stewardship and sustainable livelihoods, thereby aligning with the wider aims of the circular economy and community resilience.